Xanthine oxidase inhibitory activity from potential Malaysian medicinal plant as remedies for gout - Azmi, Saiful, M.N.; Jamal, Parveen; Amid, Azura (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Malaysia has a rich diversity of medicinal plants and some of them inhibit xanthine oxidase (XO), which can be introduced as new natural sources of gout medication and a substitute for synthetic xanthine oxidase inhibitors (XOI). The degree of XO inhibitory activity was determined by measuring the absorbance spectrophotometrically at 295 nm, which is associated with uric acid formation. Our preliminary screening study had employed the use of distilled water, 70% methanol and absolute ethanol to extract XOI from twenty parts of five plant species, namely, Averrhoa carambola, Carica papaya, Dimocarpus longan malesianus, Manilkara zapota and Salacca zalacca. These plants were selected based on their frequent medicinal usages by local folks. The results have shown that an aqueous extract of Carica papaya mature leaves has promising activity to inhibit XO up to 75.68 ± 0.1%. Statistical experimental design were employed to optimize the selected sample (dried Carica papaya leaves: distilled water) on extraction of XOI and the maximum XOI percentage of 86.93 ± 1.9% was obtained, which exhibited only 6.76% less than the activity exhibited by allopurinol (93.69 ± 0.2%), a commercial XOI. The comparison was made between allopurinol and optimized extract on the basis of IC50 concentrations. Allopurinol showed IC50 value of 3.74 μg/ml that is considerably lower as compared to the optimized sample (4.33 μg/ml).